Controversies in Obesity - Haslam, David W.; Sharma, Arya M.; le Roux, Carel W.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
Obesity is a relatively new and controversial field of medicine. Some of the controversies surrounding obesity can be dismissed as myths, others reveal the lack of consensus and comprehensive knowledge which exist in obesity and its complex relationship with diabetes and other serious long-term conditions. Controversies in Obesity takes the unique approach of assessing the controversies surrounding obesity, thus seeking to debunk the myths and highlight and explore the genuine science, whilst demonstrating areas where there is healthy debate. This book will appeal to primary care physicians, trainees and specialist nurses involved in care of the obese patient, and would be of interest to anyone who wishes to gain a better understanding of the complex nature of obesity and its management.
1. Obesity: Why Bother? -- 2. Too Late to Challenge the Modern Obesity Epidemic? -- 3. Government Action to Tackle Obesity -- 4. Why Are Governments Abdicating from Dealing with the Obesity Crisis? -- 5. Childhood Habits and the Obesity Epidemic -- 6. Obesity and Sexuality -- 7. Fat on Display -- 8. The Emerging Paradigm Shift in Understanding the Causes of Obesity -- 9. Adenoviruses and Obesity -- 10. The Role of the Gut Microbiome in Obesity -- 11. Saturated Fat in Cardiovascular Disease and Obesity: Friend or Foe? -- 12. Childhood Obesity and the Environment -- 13. Genetics and Epigenetics: Myths or Facts? -- 14. Chronicities of Modernity and the Contained Body as an Explanation for the Global Pandemic of Obesity, Diabetes, and the Metabolic Syndrome -- 15. Screening for Type 2 Diabetes -- 16. Assessing the Cardiometabolic Risk of Obesity: Importance of Visceral/Ectopic Fat and of the Use of Hypertriglyceridemic Waist -- 17. Moving Beyond Scales and Tapes: The Edmonton Obesity Staging System -- 18. Obstructive Sleep Apnea -- 19. Obesity and the Heart Disease Patient: Controversies Abound -- 20. Obesity, Diabetes and Dental Health: Relationship and Management -- 21. Very Low Calorie Diets: Saint or Sinner? -- 22. Obesity and the Mind -- 23. Adipose Tissue Expansion for Improving Glycemic Control -- 24. Should Hip and Knee Arthroplasty Be Restricted in the Obese? -- 25. Is It Time to Rename Obesity Management as Secondary Prevention? -- 26. Childhood Obesity: What Harm, Any Solutions? -- 27. Residential Weight Loss Camps for Children and Young People -- 28. Sibutramine and Rimonabant: Gone, but Is Their Passing Instructive? -- 29. Laparoscopic Adjustable Gastric Banding: The Physician$1 (Bs Choice in Bariatric Surgery -- 30. Challenges Faced by the Bariatric Multidisciplinary Team -- 31. The Controversies Around Roux-en-Y Gastric Bypass -- 32. Weight Gain on Glucose-Lowering Agents -- 33. Tipping the Scales of Truth: Why the Energy Balance Equation Is a Dangerous Lie -- 34. OTC Slimming Aids -- 35. Overcoming Sloth.s
Keywords: Medicine; Internal medicine; Diabetes; Endocrinology; Medicine & Public Health; Medicine/Public Health, general; Internal Medicine; Diabetes; Endocrinology